Investigation of the therapeutic effects and mechanisms of Houpo Mahuang Decoction on a mouse model of chronic obstructive pulmonary disease - Li, Shanlan; Dai, Ziqi; Zhang, Tong; Guo, Zhuoqian; Gao, Feng; Cheng, Xuehao; An, Jin; Lin, Yixuan; Xiong, Xiaomin; Wang, Nan; Jiang, Guanghui; Xu, Bing; et al. (Frontiers in Pharmacology, 2024)
Background: With a growing global population affected by Chronic Obstructive Pulmonary Disease (COPD), the traditional Chinese herbal formula Houpo Mahuang Decoction (HPMHD) has been used for centuries to address respiratory ailments.While studies have demonstrated the therapeutic benefits of HPMHD in COPD, the effective active ingredients, potential targets, and molecular mechanisms underlying its effectiveness remained unclear.The mechanisms of action of certain HPMHD components, targets, and pathways for the treatment of COPD were predicted using a network pharmacology method. We induced a COPD mouse model using porcine pancreatic elastase and evaluated the pathological changes and healing processes through HE and Masson staining. Immunofluorescence was used to assess the levels of IL-6 and TNF-ɑ.RNA-Seq analysis was conducted to identify differentially expressed genes (DEGs) in the lungs of normal, control, and treated mice, revealing the biological pathways enriched by HPMHD in COPD treatment. Finally, the expression of DEGs was verified using Western blotting and RT-qPCR.: HPMHD effectively alleviated pathological symptoms and improved COPD in mice by modulating the IL-17 signaling pathway. Treatment with HPMHD improved lung morphology and structure, reduced inflammatory cell infiltration, and inhibited IL-6 and TNF-ɑ levels. Network pharmacology and transcriptomics further revealed the mechanism, indicating that the IL-17 signaling pathway might been instrumental in the inhibitory effect of HPMHD on mouse model of COPD. Subsequent experiments, including protein blotting and RT-qPCR analysis, confirmed the activation of the IL-17 signaling pathway by HPMHD in the COPD mouse model, further supporting the initial findings. Conclusion: HPMHD was shown to alleviate COPD and reduce lung inflammation in mice, potentially through the activation of the IL-17 signaling pathway. This study provides a novel direction for the development of COPD drugs.